A Sentence a Day – How to Engage University Students in an Online Daily Writing Task - Sutcliffe de Moraes, Naomi J. (Nouvelle Revue Synergies Canada, 2018)
This article describes a case study of the use of a social network to engage university students learning English as a foreign language in an online sentence-a-day writing task. The research was carried out with A2 and B1-level English as a foreign language (EFL) students at a Brazilian university. The specific objectives included promoting the daily use of the type of language used for peer communication and providing some feedback. An analysis of student participation rates, overall and for each type of online activity, is presented.